A high-bandwidth low current transimpedance amplification circuit. (24th November 2021) - Liu, Hao; Dong, Chunhui; Yang, XinYing; Cheng, Feng; Zhang, Qingxian; Liao, Kaiyong; Lu, Zhigang; Gao, Zhiyu; Luo, Tingfang; Huang, Qichang; Li, Weilan
Abstract: A measuring circuit is designed based on the transimpedance amplifier. The methods of reducing parasitic capacitance and improving amplifier performance are introduced in detail. The influence of the parasitic capacitance generated by the feedback resistors on the bandwidth in the transimpedance amplification circuit is discussed. The circuit can measure the wide-dynamic-range low current ranging from 10 -13 A to 10 -5 A in four ranges. The circuit's bandwidth is up to 500 Hz when the circuit can normally work to measure a wide-range low current. The peak-to-peak amplitude of circuit noise is less than 0.22 pA. The current drift is less than 1.06 fA/ ∘ C over a temperature range of 0 ∘ C to 85 ∘ C, and the integral nonlinearity is less than 0.25%.